Adenosine A2A receptor facilitation of hippocampal synaptic transmission is dependent on tonic A1 receptor inhibition - Lopes, L. V. (2002)
Adenosine tonically inhibits synaptic transmission through actions at A1 receptors. It also facilitates synaptic transmission, but it is unclear if this facilitation results from pre- and/or postsynaptic A2A receptor activation or from indirect control of inhibitory GABAergic transmission. The A2A receptor agonist, CGS 21680 (10 nM), facilitated synaptic transmission in the CA1 area of rat hippocampal slices (by 14%), independent of whether or not GABAergic transmission was blocked by the GABAA and GABAB receptor antagonists, picrotoxin (50 [mu]M) and CGP 55845 (1 [mu]M), respectively. CGS 21680 (10 nM) also inhibited paired-pulse facilitation by 12%, an effect prevented by the A2A receptor antagonist, ZM 241385 (20 nM). These effects of CGS 21680 (10 nM) were occluded by adenosine deaminase (2 U/ml) and were made to reappear upon direct activation of A1 receptors with N6-cyclopentyladenosine (CPA, 6 nM). CGS 21680 (10 nM) only facilitated (by 17%) the K+-evoked release of glutamate from superfused hippocampal synaptosomes in the presence of 100 nM CPA. This effect of CGS 21680 (10 nM), in contrast to the isoproterenol (30 [mu]M) facilitation of glutamate release, was prevented by the protein kinase C inhibitors, chelerythrine (6 [mu]M) and bisindolylmaleimide (1 [mu]M), but not by the protein kinase A inhibitor, H-89 (1 [mu]M). Isoproterenol (30 [mu]M), but not CGS 21680 (10-300 nM), enhanced synaptosomal cAMP levels, indicating that the CGS 21680-induced facilitation of glutamate release involves a cAMP-independent protein kinase C activation. To discard any direct effect of CGS 21680 on adenosine A1 receptor, we also show that in autoradiography experiments CGS 21680 only displaced the adenosine A1 receptor antagonist, 1,3-dipropyl-8-cyclopentyladenosine ([3H]DPCPX, 0.5 nM) with an EC50 of 1 [mu]M in all brain areas studied and CGS 21680 (30 nM) failed to change the ability of CPA to displace DPCPX (1 nM) binding to CHO cells stably transfected with A1 receptors.